A SEMIOTIC ANALYSIS OF DEATH NARRATIVES IN KAFANI.ID ADVERTISING CONTENT ON TIKTOK - Syifa Fauziyah Sukma; Kholifatul Fauziah (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2025)
Death carries profound spiritual and religious significance. In the digital era, platforms like TikTok have transformed death narratives into creative marketing tools. This study aims to analyze the visual and verbal signs in TikTok content by @kafani.id and explain how ideological and cultural meanings are constructed using Roland Barthes’ semiotic theory. Using a qualitative descriptive method, this research examines 33 videos posted between June and December 2024. The results show that signs such as white shrouds, corpse imagery, capitalized typography, and emotional phrases like “Accompany Me Until the End” construct a reflective and spiritual atmosphere. Denotatively, these signs present Islamic funeral practices; connotatively, they symbolize purity, peace, and divine connection; mythically, they reflect ideological meanings of spiritual readiness and cultural values within Indonesian Islam. This study contributes to Islamic communication scholarship by showing how religious messages are embedded in digital advertising narratives, merging spirituality, culture, and marketing in contemporary media.